INCLUSIVE EDUCATION - SUCCESSFUL EDUCATION (International journal of artificial intelligence, 2024)
This article presents information on modern approaches to inclusive education, forms of organizing the education of children with disabilities, and the fact that inclusive education is the main criterion for changing the life of a disabled child.